Artificial Intelligence (AI)-Based English Language Learning: From Theory to Practice - Eisenring, Moh. Abraham Akbar (MEKONGGA: Jurnal Pengabdian Masyarakat, 2024)
Technological developments can no longer be avoided, including in the field of school education. One of the subjects that can be integrated with the use of technology is English. However, in reality, not all teachers are able to implement technology-based English learning. Limited teacher references on learning technology and inadequate facilities are the main problems faced. Through Community Service (PkM) activities, the service team introduced the use of Artificial Intelligence (AI) in English learning at a school in Palu City, Central Sulawesi. The method used in this community was the literature review method, where the service team reviewed related references, applied them to students, then draw conclusion from the community service activity that had been carried out. Relying on the great benefits and ease of implementation, the use of AI can be a leading technology for teachers to promote modern language learning. The result of the community service indicated that the integration of AI in English learning showed positive results for students, such as increasing their enthusiasm and motivation for learning English.